Analisis Kajian Hukum Tentang Otonomi Daerah Dan Penerapan Asas Otonomi Daerah - Imam Hafidz Ma'ruf; R. Ahmad Muhamad Mustain Nasoha; Ilham Khafi Nugroho; Rakhmad Fanani (Jurnal Al-Hakim: Jurnal Ilmiah Mahasiswa, Studi Syariah, Hukum dan Filantropi, 2023)
This study evaluates the Regional Autonomy laws 32 of 2004 and 23 of 2014 in light of the Republic of Indonesia's 1945 Constitution. Where the power of autonomy to manage their own households is granted to the partition of these territories. This study is normative in character and is a legal normative study. The strategy is a normative juridical strategy. Primary data, namely the 1945 Constitution of the Republic of Indonesia and in particular Law Number 32 of 2004 and Law Number 23 of 2014 respecting Regional Autonomy, as well as secondary data were used, namely library data which includes documents official books, books on Regional Autonomy and Regional Economic Development, scientific journals and so on. And tertiary data taken from encyclopedias and dictionaries. The data obtained is then analyzed using Content Analysis on laws and regulations which are primary data. Based on the results of the research and analysis that has been carried out, it can be concluded that there are several ways to apply the principle of regional autonomy that can improve welfare and cooperation between regions nationally with unbalanced regional potential conditions such as geography and human resources. Regional autonomy as one of the instruments to realize prosperity in the form of ideal cooperation.